A Systematic Review : The Effectiveness of Nebulizer Inhalation Therapy in Increasing Oxygen Saturation in Patients with Acute Respiratory Failure - Martanti, Yuniar Dwi; Purnawan, Iwan (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACTAcute respiratory failure is a critical condition that necessitates prompt intervention to improve oxygen saturation and prevent further complications. Nebulizer inhalation therapy is widely used to deliver medications directly to the respiratory tract, enhancing oxygenation and alleviating respiratory distress. This systematic review aims to evaluate the effectiveness of nebulizer inhalation therapy in improving oxygen saturation and overall clinical outcomes in patients with acute respiratory failure. Using the keywords "nebulizer inhalation," "oxygen saturation," and "acute respiratory failure", an extensive body of literature search was carried out in PubMed, GoogleScholar, and ScienceDirect.  Research released within the past ten years, including observational studies and randomized controlled trials (RCTs). Seven eligible studies focusing on oxygen saturation, respiratory distress, length of hospital stay, and mortality outcomes were systematically analyzed. The analysis revealed that nebulizer inhalation therapy, particularly using hypertonic saline and surfactants, significantly improves oxygen saturation and reduces respiratory distress. Additionally, the therapy contributes to shorter hospital stays and lower mortality rates among individuals suffering from severe respiratory failure. Nebulizer inhalation therapy is an effective intervention for increasing oxygen saturation and improving clinical outcomes in patients with acute respiratory failure. Further high-quality studies are recommended to standardize protocols and optimize its application in clinical practice. Keywords: Nebulizer Inhalation, Oxygen Saturation, Acute Respiratory Failure, Respiratory Therapy, Systematic Review, Randomized Controlled Trials.